Experimental study of open channel flows in the presence of emergent and submerged vegetation - Zhao, Kuifeng (2014)
This thesis reports an experimental study of open channel hydraulics in the presence of simulated rigid vegetation. Depending on whether the flow depth is higher than vegetation height, the thesis can be divided into two parts (1) flow through emergent vegetation, and (2) flow through submerged vegetation. For the case of emergent vegetation, the main objectives is to investigate the flow structure using different equipments (i.e., load cell, Particle Image Velocimetry, wave gauge). Significant surface fluctuation was observed during experiments. A systematic measurement of different parameters were presented. Systematic measurements show the consistency for the fluctuation of velocity, drag coefficient, and surface elevation. For the study of flow through submerged vegetation, the flow field was presented with preliminary analysis of the velocity profile. Different approaches of modifying logarithmic law were analyzed for the velocity profile in the surface layer. It starts with Chapter 1 Introduction, which briefly covers the objective and the scope of work. Chapter 2 includes the literature review of the previous studies. Chapter 3 describes the experimental setup to measure various flow parameters by applying Particle Imaging Velocimetry (PIV) techniques, load cell and wave gauges. Chapter 4 presents the flow structures in open channel flow with emergent vegetation. Chapter 5 summarizes variations in free-surface elevation measured using wave gauges. It is shown that a modified dispersion equation could be used to estimate the frequency of transverse surface waves generated due to the presence of vegetation. Different surface patterns were classified based on experimental observations. Chapter 6 provides resistance results obtained using load cell. It compares the fluctuations in different parameters including drag coefficient, velocity, and surface elevation. Chapter 7 presents the flow structures in depth limited vegetated flow. Chapter 8 provides a modification of logarithmic law to predict the velocity profile in surface layer. Chapter 9 concludes this thesis with recommendations for further investigation.